EFFECT OF ORGANIC WASTE ON GEOTECHNICAL PROPERTIES OF SOFT CLAY - Nahla Mohammed Salim; Asmaa Akram Hassan (Journal of Engineering and Sustainable Development, 2020)
Artificial soils were prepared by mixing kaolinite with different percentage of organic material (animals waste) represented by 5, 10, 15 and 20% of soil dry weight. Series of Standard tests were conducted to determine the physical and mechanical properties of the soil such as, Grain size distribution of soils, Atterberg limits, soil compaction, vane shear test and oedometer test. The test was conducted on the soil with and without organic content. The results revealed that, the organic waste have a significant effect on the physical properties of soil such as, liquid limit, plastic limit and plasticity index. In addition the organic waste have significant effect on the compression index and on the coefficient of secondary compression. The analyses were performed using two cases: The first case is using constant value of undrained shear strength (this achieved by adding different water content to the artificial soils) and the second case is using a soils at constant water content and constant dry unit weight.